The place of families : fostering capacity, equality, and responsibility - McClain, Linda C. (Harvard University Press, 2006)
"In this bold new book, Linda McClain offers a liberal and feminist theory of the relationships between family life and politics - a topic dominated by conservative thinkers. McClain agrees that stable family lives are vital to forming persons into capable, responsible, self-governing citizens. But what are the public values at stake when we think about families, and what sorts of families should government recognize and promote?"--Jacket